Ketidaktaatan Penggunaan Aturan Ejaan dan Tanda Baca dalam Skripsi Mahasiswa Universitas Riau - Hermandra, Hermandra; Zulhafizh, Zulhafizh (GERAM: Gerakan Aktif Menulis, 2017)
In some university students’ project papers, violations of rules of Indonesian language grammar are still found. The ignorance to write a grammatically correct project paper on an ongoing basis will adversely affect the quality of the students' writing. A good project paper, both its content and language use provides an overview of the insights of the students. Students must equip their cognitives in order to be able to understand the concept of the language well. This becomes the basis of observation of violation of Indonesian language rules in student's project papers of Universitas Riau through. The method used in this research is the qualitative descriptive method. The focus of observation is on the beginning parts of the project papers especially dealing. The research findings reveal that some disobedience of rules of spelling and punctuation, namely: disobedience academic title, name of the self, shortening, preposition, word absorption, foreign word, numbering, reduplication, separation marks, commas, and spaces.